Diterpene alcohol fraction of Cyperus rotundus Linn essential oil regulates Bcl-2 and Bax expression inducing apoptosis on HeLa in vitro and in silico - Susianti Susianti, Yanwirasti Yanwirasti, Eryati Darwin, Jamsari Jamsari, Arif Setiawansyah (Journal of Applied Pharmaceutical Science, 2024)
Apoptosis, or programmed cell death, is a crucial mechanism in preventing cancer growth, and one of the targets is reducing the expression of the anti-apoptotic protein Bcl-2. This study aimed to evaluate the potential of fractions from nutsedge (Cyperus rotundus) essential oil in inducing apoptosis and inhibiting the progression of cervical cancer. The researchers investigated the apoptosis-inducing activity of these fractions against the HeLa cervical cancer cell line using in vitro and in silico approaches. The cytotoxic effects were assessed through an MTT assay on HeLa cells cultured in 96-well plates. Additionally, flow cytometry with Annexin/PI staining was employed to analyze the induction of apoptosis by the fractions. The immunocytochemical staining of cells was also implemented to assess Bax and Bcl-2 expressions. The biologically active compound in fractions was screened using a molecular docking approach to Bcl-2 co-crystalized structure and their pharmacokinetics and toxicity profile were assessed. The cytotoxic activity differed significantly from each fraction. The highest cytotoxicity was observed in fraction 1 (IC50: 8.307 + 0.186 mcg/ml), and the lowest cytotoxicity was observed in fraction 4 (IC50:>500 mcg/ml). Fraction 1 decreased the Bcl-2 expression and increased the Bax expression. Molecular docking screening revealed that 5-(7a-isopropenyl-4,5-dimethyl-octahydro-inden-4-yl)-3-methyl-pent-2-en-1-ol was predicted as the main contributor to apoptosis-inducing activity of fraction 1. The supplementation of fraction 1 induces cell apoptosis on HeLa cells, indicating the potential of this fraction of nutsedge essential oil for developing an anti-cervical cancer agent.
Keywords: Diterpene alcohol, Cyperus rotundus, Apoptosis, HeLa, Bcl-2, Bax